Design for embedded image processing on FPGAs - Bailey, Donald G. (Donald Graeme), 1962-; Wiley InterScience (Online service) (New York, NY : Wiley, 2011)
"Introductory material will consider the problem of embedded image processing, and how some of the issues may be solved using parallel hardware solutions. Field programmable gate arrays (FPGAs) are introduced as a technology that provides flexible, fine-grained hardware that can readily exploit parallelism within many image processing algorithms. A brief review of FPGA programming languages provides the link between a software mindset normally associated with image processing algorithms, and the hardware mindset required for efficient utilization of a parallel hardware design. The bulk of the book will focus on the design process, and in particular how designing an FPGA implementation differs from a conventional software implementation. Particular attention is given to the techniques for mapping an algorithm onto an FPGA implementation, considering timing, memory bandwidth and resource constraints, and efficient hardware computational techniques. Extensive coverage will be given of a range of image processing operations, discussing efficient implementations and how these may vary according to the application. The techniques will be illustrated with several example applications or case studies from projects or applications I have been involves with. Issues such as interfacing between the FPGA and peripheral devices will be covered briefly, as will designing the system in such a way that it can be more readily debugged and tuned"--
"The bulk of the book will focus on the design process, and in particular how designing an FPGA implementation differs from a conventional software implementation"--
Front Matter -- Colour Plates -- Image Processing -- Field Programmable Gate Arrays -- Languages -- Design Process -- Mapping Techniques -- Point Operations -- Histogram Operations -- Local Filters -- Geometric Transformations -- Linear Transforms -- Blob Detection and Labelling -- Interfacing -- Testing, Tuning and Debugging -- Example Applications -- References -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Embedded computer systems; Field programmable gate arrays; TECHNOLOGY & ENGINEERING -- Electronics -- Microelectronics; Embedded computer systems; Field programmable gate arrays; Electronic books; Electronic resource